2014
DOI: 10.1007/s00284-014-0757-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester

Abstract: Vancomycin-resistant Enterococci (VRE) is a serious concern for public health. Serious infections with VRE have very limited effective antimicrobial therapy, and alternative treatment approaches are highly desirable. One promising approach might be the photodynamic antimicrobial chemotherapy. In the present study, we investigated the photodynamic inactivation (PDI) of two VRE strains mediated by 5-aminolevulinic acid (5-ALA) and its derivative 5-ALA methyl ester (MAL). The photodynamic damages to bacteria on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…By comparison, previous literature that used different formulations of aminolevulinic acid followed by photodynamic therapy (ala-PDI) showed contradictory results, especially on Gram-negative bacteria [36,37]. It was shown that the increase in reactive oxygen species (ROS) induced by ala-PDI promotes intracellular biopolymer leakage, photocleavage on genomic DNA, cytoplasm denaturing, and envelope injury [38].…”
Section: Resultsmentioning
confidence: 98%
“…By comparison, previous literature that used different formulations of aminolevulinic acid followed by photodynamic therapy (ala-PDI) showed contradictory results, especially on Gram-negative bacteria [36,37]. It was shown that the increase in reactive oxygen species (ROS) induced by ala-PDI promotes intracellular biopolymer leakage, photocleavage on genomic DNA, cytoplasm denaturing, and envelope injury [38].…”
Section: Resultsmentioning
confidence: 98%
“…Apart from a recent observation that S. aureus tolerated treatment with 15 consecutive cycles of passages under sublethal aPDI conditions 11 , no resistance selection for aPDI has been shown thus far. aPDI effectively eradicates a wide group of multidrug-resistant bacteria in vitro (planktonic and biofilm cultures), e.g., vancomycin-resistant Enterococcus faecalis (VRE) (5.37 log 10 unit reduction in survival) 12 , a methicillin-resistant S. aureus (MRSA) strain (5–6 log 10 unit reduction) 13 , and extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae . Effective biofilm reduction under aPDI was also documented 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 5-ALA resulted in 5.37 log 10 reduction in survival fraction for VRE clinical isolate and 5.22 log 10 for the reference E. faecalis strain. Slightly lower efficiency was observed in case of MAL treatment reaching 5.02 and 4.91 log 10 reduction in survival fraction for the clinical and reference strains, respectively [11]. Another study concerning in vitro planktonic conditions was reported by Borba et al, who described the effectiveness of erythrosine and LED lamp emitting blue wavelength light (440-480 nm).…”
Section: Enterococcus Sppmentioning
confidence: 93%